Pengaruh Financing To Deposit Ratio (FDR), Risiko Pembiayaan, Kecukupan Modal, Dana Pihak Ketiga, Suku Bunga, dan Inflasi Terhadap Profitabilitas pada Bank Umum Syariah di Indonesia - Kamelia; Eliyanora; Gustati (Akuntansi dan Manajemen, 2019)
This study aims to examine the effect of financing to deposit ratio (FDR), financing risk, capital adequacy, third-party funds, interest rates, and inflation on profitability of Islamic Commercial Banks in Indonesia. The independent variables used in this study are financing to deposit ratio (FDR), financing risk, capital adequacy, third-party funds, interest rates, and inflation. The dependent variable is the profitability that measured using the return on assets (ROA). The study population are 13 Islamic Commercial Banks that registered in the Financial Services Authorities and Indonesian Bank during 2013-2017. Determination of sample was made by applying purposive sampling method and obtaining the sample of 9 Islamic Commercial Banks. Analysis of data used is multiple regression with the help of SPSS version 20. The results showed that financing risk had a significant effect on profitability, while financing to deposit ratio (FDR), capital adequacy, third-party funds, interest rates, and inflation had no significant effect on profitability.